Semantic structures of words denoting human body organs in English EYE-EAR-NOSE-MOUTH (Versus Vietnamese) - Nguyễn Dương Nguyên Hảo.; Thái Duy Bảo, PTS (Hà Nội : Đại học Ngoại ngữ Hà Nội, 1999)
This thesis presents semantic structures of words denoting human body organs in English.
Keywords: Anh ngữ; Semantics; English thesis; Luận văn Anh ngữ; Semantic structures; English compounds; English linguistics -- Semantics